HIRA directly targets the enhancers of selected cardiac transcription factors during in vitro differentiation of mouse embryonic stem cells - Saleh, Rasha Noureldin M. (Mol Biol Rep, 2018)
HIRA is a histone chaperone known to modulate gene expression through the deposition of H3.3. Conditional knockout of Hira in embryonic mouse hearts leads to cardiac septal defects. Loss of function mutation in HIRA, together with other chromatin modifiers, was found in patients with congenital heart diseases. However, the effects of HIRA on gene expression at earlier stages of cardiogenic mesoderm differentiation have not yet been studied. Differentiation of mouse embryonic stem cells (mESCs) towards cardiomyocytes mimics some of these early events and is an accepted model of these early stages. We performed RNA-Seq and H3.3-HA ChIP-seq on both WT and Hira-null mESCs and early cardiomyocyte progenitors of both genotypes. Analysis of RNA-seq data showed differential down regulation of cardiovascular development-related genes in Hira-null cardiomyocytes compared to WT cardiomyocytes. We found HIRA-dependent H3.3 deposition at these genes. In particular, we observed that HIRA influenced directly the expression of the transcription factors Gata6, Meis1 and Tbx2, essential for cardiac septation, through H3.3 deposition. We therefore identified new direct targets of HIRA during cardiac differentiation.